(untitled) (Tempo e Argumento, 2022)
The recent past of Spain has had an important presence in the Spanish cinema since the Transition. The development and consequences of the Second Republic (1931-1936), the Civil War (1936-1939) and the Francoism have had the interest of many filmmakers since the recovery of democracy in 1975. Due to the hegemonic censorship, during dictatorship certain aspects of these periods were not reflected in the cinema, so that in the last forty years there has been an explosion of films set in them, especially during the Civil War and postwar. Likewise, films starring by children are very opportune to see the historical context from the perspective of childhood and to discover the school past. With the aim of knowing the current films that have children’s characters and take place in the aforementioned periods, it is discussed what the school of the past was like, what prototypes of teachers, students and families prevailed, what kind of subjects was taught and how the ideology of each period was in the classroom. For this, the films Secretos del corazón (Montxo Armendáriz), La lengua de las mariposas (José Luis Cuerda), You’re the One (José Luis Garci), El espinazo del diablo (Guillermo del Toro), El florido pensil (Juan José Porto), El viaje de Carol (Imanol Uribe), Los girasoles ciegos (Cuerda) and Pan negro (Agustí Villaronga), released between 1997 and 2010, are analyzed. From these considerations, current Spanish films starring by children favor the reconstruction of the historical-educational past of these stages.